2000
DOI: 10.1164/ajrccm.162.1.9909106
|View full text |Cite
|
Sign up to set email alerts
|

A Single Intrapleural Injection of Transforming Growth Factor- β2 Produces an Excellent Pleurodesis in Rabbits

Abstract: The purpose of the present study was to determine whether the intrapleural injection of transforming growth factor beta(2) (TGF-beta(2)) would produce a pleurodesis in rabbits. Single intrapleural injections of TGF-beta(2) at doses of 5.00 microg (n = 12), 1.67 microg (n = 10), 0.50 microg (n = 10), or 0.167 microg (n = 4), or of the parenteral buffer alone (n = 5) were given in a volume of 2 ml to New Zealand white rabbits. Chest tubes were left in place for at least 72 h. Pleural fluid was aspirated at 24-h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 26 publications
0
65
0
2
Order By: Relevance
“…Talc may injure the mesothelial layer or may stimulate monocytes or mesothelial cells to produce a local reaction mediated by major inflammatory cytokines [10,11]. Among the cytokines involved in the acute inflammatory response, interleukin (IL)-8 and vascular endothelial growth factor (VEGF) are the main mediators of leukocyte activation and vascular capillary response to inflammation, respectively [12][13][14], whereas transforming growth factor (TGF)-b1 and fibroblast growth factor (FGF) are involved in the activation of fibroblasts to produce and deposit collagen [15,16].…”
mentioning
confidence: 99%
“…Talc may injure the mesothelial layer or may stimulate monocytes or mesothelial cells to produce a local reaction mediated by major inflammatory cytokines [10,11]. Among the cytokines involved in the acute inflammatory response, interleukin (IL)-8 and vascular endothelial growth factor (VEGF) are the main mediators of leukocyte activation and vascular capillary response to inflammation, respectively [12][13][14], whereas transforming growth factor (TGF)-b1 and fibroblast growth factor (FGF) are involved in the activation of fibroblasts to produce and deposit collagen [15,16].…”
mentioning
confidence: 99%
“…Our studies on both rabbits [27] and sheep [28,29] revealed that intrapleural injection of small amounts of TGF-β results in better pleurodesis than does the intrapleural injection of either doxycycline or talc slurry. Pleurodesis occurs faster after TGF-β than after talc [30].…”
Section: Incubation Of Human Pleural Mesothelial Cells Withmentioning
confidence: 72%
“…Pleurodesis occurs faster after TGF-β than after talc [30]. Moreover, the pleural fluid that results from intrapleural injection of TGF-β is characterized by a much lower WBC count and LDH level than the fluid that results from intrapleural injection of doxycycline or talc slurry [27]. The lower pleural fluid WBC count and LDH level suggest there is less inflammation and this might be associated with less chest pain and fever if TGF-β were injected into humans.…”
Section: Incubation Of Human Pleural Mesothelial Cells Withmentioning
confidence: 99%
“…The pleurodesing agent was diluted to a standard volume of 2.5 mL and injected via the chest tube, followed by 1.0 mL of 0.9% NaCl solution to clear the dead space. All samples were collected by aspiration via the chest tubes 24 h after the intrapleural injections and analysed for total leukocyte counts, protein and lactate dehydrogenase (LDH) levels as described previously [11,12]. The biochemical analyses of the pleural fluid in these rabbits have been the topic of previous reports [11,12].…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…The discovery that direct intrapleural injection of TGF-b 2 produced pleurodesis effectively, promptly and with no short-term complications in both rabbit and sheep models [11][12][13][14] challenges the traditional concept that acute inflammation is an essential initiating event in fibrosis [15,16].…”
mentioning
confidence: 99%